STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU - Ilahi, Kurnia; Sembodo, Sigit Priyo; Zamroni, Afif (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
The purposes of this article are, among others, to describe and analyze the professional competence of teachers and the principal's strategy in increasing professionalism in the Primaganda Jombang High School. To achieve the above objectives, this research uses qualitative research methods with a case study approach by conducting observations, interviews, and documentation. The results of the research conducted by the author indicate that (1) the principal in improving the professional competence of teachers at the Primaganda High School Jombang is collaborative strategy, it is proven that the principal at the Primaganda Jombang High School feels good changes to the teachers at the Primaganda High School Jombang and the students. students who are recognized by the school environment compared to the previous leadership, (2) the principal can provide solutions that are acceptable to the teacher and make decisions in taking solutions to the teacher's problems. Compared to the previous year's leadership, the current leadership is much better than the 2018/2019 school year until now, (3) To carry out his strategy the principal must make teachers able to express complaints that can hinder the teaching and learning process. As is the case when teachers complain about their limitations in IT. The principal immediately provided a solution with computer courses for teachers at the Jombang Primaganda High School and brought in tutors from outside. With the computer course, the principal has carried out one of his strategies in improving the professional competence of teachers at the Primaganda High School Jombang